Dispersed city, urban morphology, and the relationship between space and society. Case study: Machala. - Riofrío Valdiviezo, Dayanna Estefanía; Zambrano Murillo, Christian Paúl (Artes: Architecture, Technology and Sustainability, 2022)
The present research work consists of the reading of the city and study of Machala through the bibliographic analysis of the urban morphology, the dispersed city, the compact city, the urban centralities, and the palpable problems at the sociospatial level, reviewing the scale at which a city must be built and the conflicts when an urban development model is not followed. The case study starts with the review of roads, urban grid, blockage, and land use to determine the errors in current planning, and how urban-social segregations have been created due to the centralities located in a single part of the city, economically empowering certain privileged sectors. Thus, its dispersion is appreciated through a methodology where the current state of the city is compared through five axes that make up the solution to the dispersed city, categorized as a compact city, to find a desired and possible solution in the current conditions of Machala, enhancing existing facilities that have transcended in a historical and representative way for citizens and the city.